IJCM_93A: Anthropometric profile of under five children attending Pediatric at rural health training centre in Aligarh (U.P.) - Bilal Mohammad; Abedi Ali Jafer; Nawab Tabassum; Eram Uzma; Mehnaz Saira; Hashmi Syed Sohaib (Wolters Kluwer Medknow Publications, 2024)
Background: Child undernutrition is a global health concern. Malnutrition continues to be one of the leading causes of morbidity and mortality worldwide, particularly in developing countries like India. As per the NFHS-V, the prevalence of stunting, wasting and underweight in under-five children stands at 35.5%, 19.3% and 32.1% respectively. Anthropometry has become a practical tool for evaluating the nutritional status of populations, particularly of children in developing countries & the nutritional status is the best indicator of global well-being of children. Objective: To describe the anthropometric profile and assess malnutrition using anthropometric measurements of under-five children attending pediatric OPD at Rural Health Training Centre (RHTC), Jawan under Department of Community Medicine, JNMCH, A.M.U., Aligarh (U.P.). Methodology: This is a retrospective study with secondary analysis of anthropometric data of 255 under five children attending pediatric clinic for the first time at RHTC, Jawan, under Department of Community Medicine from January 1, 2023, to June 30, 2023. Collected data were entered into Microsoft Excel and analyzed by using the software SPSS, version 20.0. Results: The median age of the children was 24 months. 52.2% of them were boys and 47.8% were girls. Severe wasting (weight-for-height<-3SD) and severe stunting (height-for-age<-3SD) was present in 4.3% and 10.2% of all children respectively and there was no significant difference among different age groups. Prevalence of underweight and stunting was highest in children less than 6 months. Conclusion: Undernutrition is common in under-five children and 10.2% of children had severe wasting. In order to prevent severe forms of undernutrition health education to caregivers on various forms of undernutrition is crucial. IEC activities and health education regarding infant and young child feeding (IYCF) should be strengthened, especially to caregivers of children less than 6 months.